2021
DOI: 10.1186/s12882-021-02591-9
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of physical activity and technology enabled exercise interventions among people with advanced chronic kidney disease: a qualitative study

Abstract: Background Exercise improves health outcomes and quality of life in persons with chronic kidney disease (CKD). The numbers of persons with advanced CKD meeting physical activity guidelines however is low. We undertook a qualitative study of men and women aged 36–74 from various race/ethnic populations with advanced CKD not requiring dialysis to describe their experiences and opinions around prior physical activity, motivating factors for and barriers to exercise, and perceptions of exercise-pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“… 24 Consistent with prior studies that utilized wearable devices, 6 , 7 , 10 we found positive engagement between the participants and the watch devices. While prior work shows there remain certain barriers with technology-assisted prehab programs, such as patient confusion with mobile devices, disinterest in technology, or that mobile applications were not responsive to older patients’ needs, 12 we found that most enrolled patients liked using the Apple Watch and that BeFitMe™ Watch app was helpful for their exercise needs. Perhaps this is because it may be easier to engage in physical activity by wearing a watch rather than holding a smartphone.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“… 24 Consistent with prior studies that utilized wearable devices, 6 , 7 , 10 we found positive engagement between the participants and the watch devices. While prior work shows there remain certain barriers with technology-assisted prehab programs, such as patient confusion with mobile devices, disinterest in technology, or that mobile applications were not responsive to older patients’ needs, 12 we found that most enrolled patients liked using the Apple Watch and that BeFitMe™ Watch app was helpful for their exercise needs. Perhaps this is because it may be easier to engage in physical activity by wearing a watch rather than holding a smartphone.…”
Section: Discussionmentioning
confidence: 60%
“… 6 , 7 While various health interventions utilizing technology have successfully demonstrated feasibility and acceptability, 6 11 including among the older adult population, 7 , 9 , 10 there remain challenges with technology-assisted prehab programs unique to older adults, such as patient confusion with mobile devices, disinterest or lack of confidence in using technology, or lack of designs addressing older patients’ needs. 12 …”
Section: Introductionmentioning
confidence: 99%
“…Evidence for this can be seen in other studies in which older people 'seemed to want to disregard their limitations even while speaking about them' (Torres & Hammarström, 2006) and reported simultaneous feelings of enthusiasm and apprehension about technology (Vaportzis et al, 2017). Perceptions that technology is designed for and by young healthy people may exacerbate this apprehension (Weber et al, 2021), as may 'stereotype threat' where fear of conforming to a negative stereotype can undermine competency (Lamont et al, 2015). Some argue that technology is itself inherently paradoxical, for example, functioning as both a mitigator and exacerbator of vulnerability (Yap et al, 2021).…”
Section: Discussionmentioning
confidence: 89%
“… 71 Furthermore, three papers explored consumers’ preferences on more than one type of technology, including telephone call and mobile application 70 ; information communication technologies and website 68 ; and activity trackers and mobile applications. 72 A description of the function of each type of DHI was included in online supplemental table S5 .…”
Section: Resultsmentioning
confidence: 99%